Taking a Glimpse Into the Future by Playing?. (June 2019) - Lohmann, Robert
Background . This article analyses whether an experimentalpolicy-simulation might help political scientists inmaking predictions about prospective situations . Within the presented simulation-game, two groups of randomly assigned participants discussed the same issues but had different demographic structures. The ways in which their discussions transpired and results of the negotiation might provide a glimpse at how decisions might be made by societies in the future. Purpose . This article presents this special simulation-game. Furthermore, it seeks to discuss whether policy-simulations can be designed as experiments, whether there is a benefit, and for whom. Method . This study is based on bothqualitative and quantitative data . The partici-pants in the simulation-game have been questioned in a pretest and in two post-tests. Furthermore, six pre- and post-interviews were conducted with involved experts. Results . The results show that the simulation-game can provide some ideas about the future, if perhaps not necessarily a wholly accurate image of the future. Observing experts and the participants gained some knowledge about how future generations might work together and where potential conflicts might be. Conclusion .Policy-simulations can be designed as experiments and might help to provide a glimpse into future, but designing such simulation-games is even more com-plex than designing simulationgames for a solely educational use.